Magnetic susceptibility of an exactly solvable anisotropic spin ladder system - Tonel, A. P.; Dahmen, SR; Foerster, A.; Malvezzi, André Luiz [UNESP] (E D P Sciences, 2003)
We investigate the thermodynamics of an integrable spin ladder model which possesses a free parameter besides rung and leg couplings. The model is exactly solvable by means of the Bethe ansatz and exhibits a phase transition between a gapped and a gapless spin excitation spectrum. The magnetic susceptibility is obtained numerically and its dependence on the anisotropy parameter is determined. The spin gap obtained from the susceptibility curve and the one obtained from the Bethe ansatz equations are in very good agreement. Our results for the magnetic susceptibility fit well the experimental data for the organometallic compounds (5IAP)(2)CuBr4 . 2H(2)O (Landee C. P. et al., Phys. Rev. B, 63 (2001) 100402(R)) Cu-2(C5H12N2)(2)Cl-4 (Hayward C. A., Poilblanc D. and Levy L. P., Phys. Rev. B, 54 (1996) R12649, Chaboussant G. et al., Phys. Rev. Lett., 19 ( 1997) 925; Phys. Rev. B, 55 ( 1997) 3046.) and (C5H12N)(2)CuBr4 (Watson B. C. et al., Phys. Rev. Lett., 86 ( 2001) 5168) in the strong-coupling regime.